Neutral Wind Profiles During Periods of Eastward and Westward Equatorial Electrojet. Issue 11 (5th June 2021) - Yamazaki, Y.; Harding, B. J.; Stolle, C.; Matzka, J.
Abstract: The equatorial electrojet (EEJ) is a band of zonal electric current flowing along the magnetic equator in the dayside E‐region ionosphere. The direction of the EEJ is often eastward but sometimes westward. The mechanism for generating westward EEJ is not fully understood. This study examines the relationship between the eastward/westward EEJ and equatorial neutral winds using simultaneous observations of the EEJ from the European Space Agency's Swarm satellite mission and thermospheric winds from the Michelson Interferometer for Global High‐resolution Thermospheric Imaging on NASA's Ionospheric Connection Explorer mission during December 2019–January 2021. Significant differences are found in the average zonal wind profiles between times of eastward and westward EEJ. The EEJ intensity correlates negatively ( R = −0.54) and positively ( R = 0.58) with the eastward wind velocities at ∼110 and ∼140 km, respectively. The results suggest that the modulation of the zonal electric field by the equatorial zonal wind plays a role in producing the westward EEJ. Plain Language Summary: Electric fields and currents in the dayside E‐region ionosphere arise from collisional interactions between neutral and plasma particles; thus understanding electrodynamic processes in the ionosphere can greatly benefit from simultaneous measurements of neutral and plasma parameters. This study explores simultaneous observations of equatorial ionospheric currents from the European Space Agency's Swarm satellite mission and equatorial neutral winds from the Michelson Interferometer for Global High‐resolution Thermospheric Imaging on NASA's Ionospheric Connection Explorer mission. It is found that the average vertical profiles of the zonal wind are significantly different between periods of eastward and westward equatorial currents. The results highlight the importance of the equatorial zonal wind in driving changes in the equatorial ionosphere. Key Points: Simultaneous observations of the equatorial electrojet (EEJ) by Swarm and thermospheric winds by Ionospheric Connection Explorer/Michelson Interferometer for Global High‐resolution Thermospheric Imaging are analyzed Significant differences are found in the average zonal wind profiles between times of eastward and westward EEJ Modulation of the zonal electric field by the equatorial zonal wind plays a role for westward EEJ